2010
DOI: 10.1002/bip.21401
|View full text |Cite
|
Sign up to set email alerts
|

Peptide reporters of kinase activity in whole cell lysates

Abstract: Kinase assays are used to screen for small-molecule inhibitors that may show promise as targeted pharmaceutical therapies. Using cell lysates instead of purified kinases provides a more accurate estimate of inhibitor sensitivity and selectivity in a biological setting. This review summarizes the range of homogeneous (solution-phase) and heterogeneous (solid-supported) formats available for using peptide substrates to monitor kinase activities in cell lysates. With a focus on heterogeneous kinase assays, the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 92 publications
(93 reference statements)
0
27
0
Order By: Relevance
“…In particular, streptavidin on the bead surface may occlude the bound peptide substrate from easy access to kinases in solution. In general, solid-phase kinase assays have been characterized as less efficient that solution-phase kinase reactions [46]. Post-reaction capture of phosphorylated substrates, after solution-phase kinase reactions, has been used as an alternative to solid-phase kinase assays.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, streptavidin on the bead surface may occlude the bound peptide substrate from easy access to kinases in solution. In general, solid-phase kinase assays have been characterized as less efficient that solution-phase kinase reactions [46]. Post-reaction capture of phosphorylated substrates, after solution-phase kinase reactions, has been used as an alternative to solid-phase kinase assays.…”
Section: Resultsmentioning
confidence: 99%
“…[11] The substrate portion (bold) is relatively selective for the c-Abl kinase (Abl1) over other tyrosine kinases, however it is phosphorylated by the Abl family member named Abl-related gene (Arg, also known as Abl2). [12] Abl1 and Abl2 are highly homologous and share many functions in normal cells. [13] In this work, “Abl kinase” denotes both Abl1 and Abl2.…”
mentioning
confidence: 99%
“…Previous work using immobilized Abltide to measure Bcr-Abl activity in cell lysates demonstrated that altered orientations resulted in increased signal intensities (35). It was also shown that inclusion of p40, the high-affinity peptide ligand for the Abl kinase SH3 domain, led to more efficient phosphorylation of Abltide (17, 36).…”
Section: Resultsmentioning
confidence: 99%